AN ANALYSIS OF THE FARMERS CHOICE OF CREDIT SOURCE IN KANO STATE: A MICRO LEVEL ANALYSIS (AUN INTERNATIONAL CONFERENCE, 2025)
Access to agricultural credit remains a significant barrier to productivity and rural development in Nigeria. This study investigates the determinants of farmers’ choice of credit sources in Kano State using a microeconometric framework. A stratified-cluster sample of 1,000 farmers across urban, semi-urban, and rural areas was surveyed. A multinomial logit model was employed to examine the influence of demographic, socioeconomic, and institutional variables on farmers’ choice among self-financing, informal credit, microfinance, commercial banks, and government sources. Results reveal that urban residence, profitability, political affiliation, and occupation strongly influence access to formal credit. Subsistence farmers and those with lower education are more likely to rely on informal or personal financing. The study provides evidence-based recommendations for inclusive agricultural credit policy and financial infrastructure development targeting smallholder farmers